(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of pedagogical skills in relation to the reflective thinking process of teachers in Cluster 16, Davao City Division. The study used a non-experimental descriptive-correlational research design, utilizing an adapted survey instrument to gather responses from the randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r and Simple Linear Regression Analysis. Findings revealed that the teachers’ pedagogical skills in terms of strategies in classroom communication, promote fairness, respect and care, establish learning environment, application of knowledge of content is extensive, and likewise, reflective thinking process of teachers in terms of choosing the best solution available, defining the problem, teasing out a possible solution, analyzing the problem and naming the needs for the solution is extensive. There was a significant relationship between teachers’ pedagogical skills and reflective thinking processes. Domains of teachers’ pedagogical skills in terms of application of knowledge of content, strategies in classroom communication, promote fairness, respect, and care significantly influenced the reflective thinking process of teachers. Future research may engage in partnerships to implement and evaluate interventions to enhance pedagogical skills and reflective thinking in real-world educational settings. Identify effective strategies and interventions that enhance pedagogical skills and promote reflective thinking among teachers. Share research findings with educational institutions, policymakers, and professional development providers to inform practice